Inovações tecnológicas em cadeias agroindustriais: alguns casos do segmento de processamento de carnes, leite e café no Brasil - Santini, Giuliana Aparecida; de Souza Filho, Hildo Meirelles; Bánkuti, Sandra Mara Schiavi (Revista Gestão da Produção Operações e Sistemas, 2006)
The main objective of this paper is to identify and characterize the technological innovations from the meat,milk and coffee productive chain processing sector, based on authors discussing the innovation economy. Themechanisms are utilized by the companies in order to obtain the technological information, generatetechnologies, as well as form cooperative arrangements for the technological development. Semi-structuredquestionnaires were applied in 34 companies belonging to five productive chains (milk, chicken, swine, cattleand coffee). Some results could be confirmed regarding innovation. Four innovation standards were found:adaptations by multinational companies; innovations mirrored in the internal market; innovations mirroredin the international market and authentically national innovations. It was observed that the companies developmainly incremental innovations, and that such innovations are mostly based on suppliers (input orequipment). However, there are also internal efforts to the company in order to generate changes in productsand in the process. It was also observed that the formation of partnerships / cooperation is relevant to theevolution of the innovation process in the sector. In addition, in several cases the innovation is clearly a functionof the market structures of which the companies are part.Keywords: Technological innovation; Agroindustry; Partnerships.